Micro-molecular cyclophosphazene intumescent flame retardant with ultraviolet shielding performance and preparation method of micro-molecular cyclophosphazene intumescent flame retardant
By developing small-molecular cyclophosphazene expanded flame retardant with high nitrogen and phosphorus content, the problems of aging and insufficient flame retardant performance of polymer materials under ultraviolet light are solved, and the efficient flame retardant and ultraviolet shielding effect is achieved, which improves the material's Mechanical properties and compatibility.
Patent Information
- Application Number
- CN202411489575.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polymer materials have accelerated aging under ultraviolet irradiation, and their flame retardant performance is poor. The flame retardant efficiency and compatibility of small-molecular flame retardants are low, which can easily lead to environmental pollution and life safety threats.
Develop a small molecule cyclophosphazene expansion flame retardant, which is prepared by reacting 2-aminopyrazine with hexachlorocyclotriphosphazene to form a multi-ring structure flame retardant with high nitrogen and phosphorus content, collecting acid source and gas The source and carbon source are integrated to improve flame retardant efficiency and ultraviolet shielding performance.
This flame retardant significantly improves the flame retardant effect and mechanical properties of polymer materials, delays the material aging process, enhances compatibility with polymer systems, and reaches the flame retardant level of UL-94 V-0.
Smart Images

Figure CN119462767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance and a preparation method thereof, belonging to the technical field of flame retardant materials. Background Art
[0002] Ultraviolet rays, with their unique wavelength characteristics, play an important role in human life and scientific research. They have the advantages of sterilization, promoting the production of vitamin D in the human body, and improving sleep. However, for polymer materials, ultraviolet irradiation presents a complex double-edged sword effect. The high energy of ultraviolet rays is enough to cause the breakage and degradation of polymer chain segments, resulting in changes in the structure and properties of the molecular chain and accelerating the aging process of the material. Long-term exposure to ultraviolet rays will not only cause a significant decrease in strength of polymer materials, but also may cause color changes due to photooxidation reactions, lose their original physical, chemical properties and aesthetic characteristics, and pose a serious threat to the stability and functionality of the materials. Polymer materials have become one of the most widely used materials in the world today due to their advantages such as light weight, high strength, easy processing and excellent chemical stability. Whether it is used in the medical field to manufacture various artificial organs and medical equipment, or as materials for reactors and pipelines in the chemical field, polymer materials play an indispensable role. With the advancement of science and technology, new polymer materials emerge in an endless stream, and their unique physical and chemical properties continue to expand the application field of materials. However, a significant weakness of polymer materials is their poor flame retardancy. Under fire conditions, polymer materials will not only burn rapidly, releasing a large amount of heat and exacerbating the spread of fire, but may also release toxic smoke and gases, posing a huge threat to people's lives and safety.
[0003] In view of this situation, improving the flame retardant and anti-aging properties of polymer materials has become a research focus in the field of materials science. By adding various flame retardants, such as phosphorus, halogen and inorganic flame retardants, the flame retardancy of materials can be significantly improved. These flame retardants can inhibit the spread of flames, slow down the heat release rate, and reduce the generation of toxic gases to a certain extent. The aging process of epoxy resin can be inhibited by adding ultraviolet shielding agents. But at the same time, the addition of additives also brings a series of new challenges, including the smoke generated during the combustion process will pollute the environment, the compatibility with the polymer matrix will also decrease, and there will be potential negative effects on other properties of the material (such as mechanical strength and processing properties). In view of these problems, researchers are committed to developing new flame retardant technologies. For example, by introducing nano-scale flame retardant particles to achieve a more efficient flame retardant effect; by molecular design, the polymer material itself has flame retardant properties. The research and development and application of these flame retardant technologies provide broad prospects for improving the application of polymer materials, and are expected to significantly reduce fire accidents caused by polymer materials in the future.
[0004] However, small molecule flame retardants have exposed several problems during their application. First, due to the growing demand for flame retardant properties, their usage has increased significantly, which not only increases costs, but may also bring new safety hazards and pollute the environment. Secondly, many small molecule flame retardants have low flame retardant efficiency and are difficult to meet the requirements of modern industry and consumers for higher safety standards. In addition, these small molecule flame retardants generally have poor compatibility with the matrix and are easily precipitated from the material. The precipitated flame retardants may pollute the environment and produce a large amount of smoke and toxic gases when burned, resulting in reduced flame retardant efficiency and posing a threat to human life safety. At the same time, some small molecule flame retardants have a relatively single function and can only be used as flame retardant components. They are also easy to destroy the mechanical properties of the system. Therefore, when seeking solutions to improve the flame retardant properties of materials, these shortcomings of small molecule flame retardants must be comprehensively considered to explore more effective, environmentally friendly, economical and multifunctional options.
[0005] Elements such as phosphorus and nitrogen in flame retardants can not only enhance flame retardancy, but also easily form hydrogen bonds with epoxy groups, which enhances the π-π conjugation between flame retardants and macromolecular chains. Therefore, while maintaining flame retardancy, they can significantly improve the mechanical properties and UV shielding properties of polymers. Phosphazene flame retardants are a class of compounds with alternating phosphorus and nitrogen atoms as the main chain structure, with cyclic or linear structures and good flame retardant effects. Phosphazene flame retardants have good thermal stability, antioxidant properties, biocompatibility and biodegradability, as well as excellent optical and mechanical physical properties. They have PN synergistic flame retardancy and can give materials excellent properties. Among them, hexachlorocyclotriphosphazene is a cyclophosphazene with phosphorus and nitrogen atoms as the skeleton. Its six-membered ring has strong stability, which makes it have good high temperature resistance and flame retardancy. At the same time, the π-π conjugation formed by the phosphorus and nitrogen rings is conducive to enhancing the absorption capacity of ultraviolet rays. At present, no high-phosphorus and nitrogen-content intumescent flame retardants based on hexachlorocyclotriphosphazene have been reported. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance and a preparation method thereof. The flame retardant is a small molecule cyclophosphazene intumescent flame retardant that integrates an expansion system (including an acid source, a gas source, and a carbon source). The flame retardant contains higher nitrogen and phosphorus content, has higher flame retardant efficiency, and its decomposition temperature is similar to that of the polymer material, so that it can better play a synergistic role and improve the flame retardant effect; at the same time, it adopts a multi-ring structure synthesis to increase the content of large π bonds in the system, giving the flame retardant a more excellent ultraviolet absorption ability, which can effectively delay the aging process of the polymer material while promoting the compatibility of the flame retardant and the polymer system, and further improve the mechanical properties of the matrix. Compared with the existing single-chain or branched phosphorus / nitrogen flame retardants, the small molecule cyclophosphazene flame retardant has excellent flame retardant effect and also has the effects of high mechanical properties and anti-aging ability.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance, the molecular formula of the flame retardant is C 24 H 24 N 21 P3, structural formula:
[0009]
[0010] A method for preparing the small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance according to the present invention, the method steps comprising:
[0011] 2-aminopyrazine is dissolved in an organic solvent and mixed evenly, then heated to 55-80°C, a hexachlorocyclotriphosphazene solution is added, and the reaction is continued by heating, stirring and reflux for 8-24 hours. After the reaction is completed, the precipitate is collected, washed and vacuum dried to obtain a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance.
[0012] Preferably, the molar ratio of the hexachlorocyclotriphosphazene to 2-aminopyrazine is 1:6 to 9. More preferably, the molar ratio of the hexachlorocyclotriphosphazene to 2-aminopyrazine is 1:6.5 to 7.5.
[0013] Preferably, the organic solvent is one or more of tetrahydrofuran, anhydrous acetonitrile, acetone and dichloromethane.
[0014] Preferably, the solvent of the hexachlorocyclotriphosphazene solution is tetrahydrofuran.
[0015] Preferably, the hexachlorocyclotriphosphazene solution is added within 30 minutes.
[0016] Preferably, the reaction temperature is 60-70° C. and the reaction time is 12-18 h.
[0017] Preferably, the stirring rate is 300-400 rpm.
[0018] Preferably, the drying temperature is 50-70° C. and the drying time is 8-16 hours.
[0019] An application of the small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance described in the present invention, wherein the flame retardant is used as a flame retardant for a polymer system.
[0020] Beneficial Effects
[0021] The invention provides a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance and a preparation method thereof, which has a higher phosphorus and nitrogen content, wherein the nitrogen content is 42.05% and the phosphorus content is 13.28%. The flame retardant is a high-efficiency intumescent flame retardant integrating three sources (acid source, gas source, carbon source), does not need to be compounded with other flame retardants, and has a certain amount of improvement on the mechanical properties of epoxy resin after addition. The flame retardant is obtained by reacting 2-aminopyrazine with hexachlorocyclotriphosphazene.
[0022] Adding a small amount of the flame retardant of the present invention to a polymer matrix can significantly improve the ultraviolet shielding performance of the polymer system, and for the epoxy resin system, the ultraviolet shielding ability can be increased by 2 times. In the flame-retardant epoxy resin, when the addition amount is 2%, the vertical combustion test grade can reach UL-94V0 level; after adding the flame retardant, the peak heat release rate can be reduced by 41.6%, and the total heat release can be reduced by 23.9%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the H-NMR spectrum of the small molecule cyclophosphazene intumescent flame retardant synthesized in Example 1 of the present invention.
[0024] Figure 2 This is the nuclear magnetic phosphorus spectrum of the small molecule cyclophosphazene intumescent flame retardant synthesized in Example 1 of the present invention.
[0025] Figure 3 This is the infrared spectrum of the small molecule cyclophosphazene intumescent flame retardant synthesized in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The present invention will be further described in detail below in conjunction with specific embodiments.
[0027] Example 1
[0028] Weigh 20 g (0.21 mol) of 2-aminopyrazine and dissolve it in 280 mL of tetrahydrofuran solution, stir until it is clear without precipitation, as solution A; then add solution A to a 500 mL three-necked flask, connect a 100 mL constant pressure dropping funnel, a magnetic stirrer, a 24-mouth serpentine condenser, and a tail gas receiving and processing device, stir and heat at 70 ° C; dissolve 10 g (0.03 mol) of hexachlorocyclotriphosphazene in 70 mL of tetrahydrofuran solution, and stir at room temperature and pressure. The mixture was stirred under stirring until it became clear and transparent as solution B; solution B was then added to the constant pressure funnel, the flow rate was adjusted to drip for 30 min, the reaction was continued with stirring for 24 h, the precipitate was filtered, and then washed alternately with 10 mL of tetrahydrofuran and 10 mL of acetone for three times, and then dried in a vacuum oven at 60° C. and 1 KPa for 12 h to obtain 24.93 g of reddish brown powder with a yield of 83.1%, which is a small molecule cyclophosphazene intumescent flame retardant with UV shielding properties.
[0029] The nuclear magnetic hydrogen spectrum, nuclear magnetic phosphorus spectrum and infrared spectrum of the reddish brown powder are as follows Figure 1-3 As shown, the results show that C 24 H 24 N 21 P3, structural formula:
[0030]
[0031] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0032] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 32.5%. The flame retardant grade obtained by the vertical combustion experiment test (UL-94) was V-0. Further cone calorimeter test was carried out, and the peak heat release rate was reduced by 43.2% relative to the pure epoxy system, the total heat release was reduced by 21.3% relative to the pure epoxy system, the carbon dioxide yield was reduced by 51%, and the carbon monoxide yield was reduced by 57%. The epoxy system was also subjected to mechanical property tests and UV diffuse reflection tests. The results showed that the tensile strength of the epoxy composite system was increased by 27.4% compared with pure epoxy resin, and the UV transmittance was reduced by 58%.
[0033] Example 2
[0034] Weigh 20g (0.21mol) of 2-aminopyrazine, dissolve it in 280mL tetrahydrofuran solution, stir until clear without precipitation, as solution A, then add solution A to a 500mL three-necked flask, connect a 100mL constant pressure dropping funnel, magnetic stirring, 24-mouth serpentine condenser, and tail gas receiving and processing device, and stir and heat at 70°C. Dissolve 10g (0.03mol) of hexachlorocyclotriphosphazene in 70mL tetrahydrofuran solution, stir until clear and transparent at room temperature and pressure, as solution B, then add solution B to a constant pressure funnel, adjust the flow rate for 30min to drip, continue stirring and reacting for 18h, filter the precipitate, wash it three times with 10mL tetrahydrofuran and 10mL acetone alternately, and then dry it in a vacuum oven at 60°C and 1KPa for 12h to obtain 22.65g of reddish brown powder with a yield of 75.5%. It is a small molecule cyclophosphazene intumescent flame retardant with UV shielding properties.
[0035] The results of H NMR spectrum, P NMR spectrum and IR spectrum of the reddish brown powder indicate that the structural formula of the flame retardant is the same as that of Example 1.
[0036] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0037] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 31.7%. The flame retardant grade obtained by the vertical combustion test (UL-94) was V-0. Further cone calorimeter testing was carried out, and the peak heat release rate was reduced by 40.7% relative to the pure epoxy system, the total heat release was reduced by 20.3% relative to the pure epoxy system, the carbon dioxide yield was reduced by 56%, and the carbon monoxide yield was reduced by 59%. The epoxy system was also subjected to mechanical property tests and ultraviolet diffuse reflection tests. The results showed that the tensile strength of the epoxy composite system was increased by 28.1% compared with pure epoxy resin, and the ultraviolet transmittance was reduced by 52%.
[0038] Example 3
[0039] Weigh 10g (0.105mol) of 2-aminopyrazine, dissolve it in 140mL tetrahydrofuran solution, stir until clear without precipitation, as solution A, then add solution A to a 250mL three-necked flask, connect a 50mL constant pressure dropping funnel, magnetic stirring, 24-mouth serpentine condenser, and tail gas receiving and processing device, and stir and heat at 70°C. Dissolve 5g (0.015mol) of hexachlorocyclotriphosphazene in 35mL tetrahydrofuran solution, stir until clear and transparent at room temperature and pressure, as solution B, then add solution B to a constant pressure funnel, adjust the droplet flow rate for 30min to drip, continue stirring and reacting for 12h, filter the precipitate, and then wash it three times with 10mL tetrahydrofuran and 10mL acetone alternately, and then dry it in a vacuum oven at 60°C and 1Kpa for 12h to obtain 12.54g of reddish brown powder with a yield of 83.6%. It is a small molecule cyclophosphazene intumescent flame retardant with UV shielding properties.
[0040] The results of H NMR spectrum, P NMR spectrum and IR spectrum of the reddish brown powder indicate that the structural formula of the flame retardant is the same as that of Example 1.
[0041] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After about 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0042] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 33.1%. The flame retardant grade obtained by the vertical combustion test (UL-94) was V-0. Further cone calorimeter test was carried out, and the peak heat release rate was reduced by 45.7% relative to the pure epoxy system, the total heat release was reduced by 24.1% relative to the pure epoxy system, the carbon dioxide yield was reduced by 55%, and the carbon monoxide yield was reduced by 53%. The epoxy system was also subjected to mechanical property tests and UV diffuse reflection tests. The results showed that the tensile strength of the epoxy composite system was increased by 23.6% compared with pure epoxy resin, and the UV transmittance was reduced by 49%.
[0043] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance, characterized in that: The molecular formula of the flame retardant is C 24 H 24 N 21 P3, structural formula:
2. A method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 1, characterized in that: The method steps include: 2-aminopyrazine is dissolved in an organic solvent and mixed evenly, then heated to 55-80°C, a hexachlorocyclotriphosphazene solution is added, and the reaction is continued by heating, stirring and reflux for 8-24 hours. After the reaction is completed, the precipitate is collected, washed and vacuum dried to obtain a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance.
3. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The molar ratio of the hexachlorocyclotriphosphazene to 2-aminopyrazine is 1:6-9.
4. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 3, characterized in that: The molar ratio of the hexachlorocyclotriphosphazene to 2-aminopyrazine is 1:6.5-7.
5.
5. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The organic solvent is one or more of tetrahydrofuran, anhydrous acetonitrile, acetone and dichloromethane; the solvent of the hexachlorocyclotriphosphazene solution is tetrahydrofuran.
6. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The hexachlorocyclotriphosphazene solution was added completely within 30 minutes.
7. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The reaction temperature is 60-70°C and the reaction time is 12-18h.
8. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The stirring rate is 300-400 rpm.
9. The method for preparing a small molecule cyclophosphazene intumescent flame retardant with ultraviolet shielding performance as claimed in claim 2, characterized in that: The drying temperature is 50-70°C and the drying time is 8-16 hours.
10. An application of the small molecule cyclophosphazene intumescent flame retardant with UV shielding performance as claimed in claim 1, characterized in that: The flame retardant is used as a flame retardant for a polymer system.